(untitled) (Journal of Plant Disease Sciences, 2023)
A roving survey was conducted in different districts of Upper Brahmaputra Valley Zone of Assam in order to ascertain the presence of Citrus Greening disease (CGD) and characterization of their causative agents through molecular assays. The typical symptoms observed in field conditions were blotchy mottling, small and upright leaves, yellowing of leaves and chlorosis, pre-mature fruit drop, twig dieback. Disease severity calculated on the basis of the disease rating scale indicated that the severity of CGD in young and matured Khasi mandarin was found to be highest in Jorhat district (33.75%) and Golaghat district (41.26%) respectively. Lowest disease severity of 16.66 per cent was recorded in Dibrugarh district for both young and matured plants. PCR assays of the samples for CGD diagnosis showed that overall 13 out of 44 samples from young and 42 out of 60 samples from matured Khasi mandarin were infected. The desired 703bp PCR product using the primer pair A2/J5 confirmed the presence of Candidatus Liberibacter asiaticusin the surveyed areas.